Effects of the herb mixture, DTS20, on oxidative stress and plasma alcoholic metabolites after alcohol consumption in healthy young men - Yang Hee Hong (Integrative Medicine Research)
Background: This study was designed to investigate the effect of a herbal mixture extract (DTS20) on the attenuation of oxidative stress and hangover after alcohol consumption in healthy volunteers. Methods: DTS20 consists of Viscum album L. (40%), Lycium chinense L. (30%), Inonotus obliquus (20%), and Acanthopanax senticosus H. (10%). We recruited healthy, nonsmoking, adult men volunteers aged between 21 years and 30 years to participate in a crossover trial. Twenty participants received either one package of placebo with 200 mL water or DTS20 with 200 mL water. Thirty minutes later, the volunteers ingested one bottle of Soju, which is a commercially available liquor (19% alcohol in 360 mL). Results: Volunteers received the opposite treatment after a 1-week washout period. DTS20 is mainly composed of sugars (564.5 mg/g) and polyphenol (28.2 mg/g). Alcohol levels in the DTS20 group were significantly lower than the control group at 2 hours after drinking Soju (p < 0.05). Acetaldehyde levels in the DTS20 group tended to be lower than the control group at 2 hours after drinking Soju, but was not significantly different. The antioxidant activity level was also significantly different between the control and DTS20 group 2 hours after drinking Soju (p < 0.05). No differences in plasma alanine transaminase or aspartate transaminase levels were observed between plasma levels before drinking and 2 hours after drinking Soju in the control group. Conclusion: It was concluded that DTS20 reduced oxidative stress and hangover by mitigating plasma alcohol concentrations and elevating antioxidative activity in healthy male adults.